Application value of blood metagenomic next-generation sequencing in patients with connective tissue diseases - Su, Rui; Yan, Huanhuan; Li, Na; Ding, Tingting; Li, Baochen; Xie, Yuhuan; Gao, Chong; Li, Xiaofeng; Wang, Caihong (Frontiers in Immunology, 2022)
Objective This study aimed to analyze the application value of blood metagenomic next-generation sequencing (mNGS) in patients with connective tissue diseases (CTDs) to provide a reference for infection diagnosis and guidance for treatment. Methods A total of 126 CTD patients with suspected infections who were hospitalized in the Department of Rheumatology, the Second Hospital of Shanxi Medical University from January 2020 to December 2021 were enrolled in this study. We retrospectively reviewed the results of mNGS and conventional diagnostic tests (CDTs). Results Systemic lupus erythematosus (SLE) and polymyositis/dermatomyositis (DM/PM) had the highest incidence of infections. The positive pathogen detection rates of mNGS were higher than those of CDT. The virus infections are the most common type in CTD patients with single or mixed infection, especially Human gammaherpesvirus 4 (EBV), Human betaherpesvirus 5 (CMV), and Human alphaherpesvirus 1. The incidence of prokaryote and eukaryote infections is secondary to viruses. Bloodstream infections of rare pathogens such as Pneumocystis jirovecii should be of concern. Meanwhile, the most common mixed infection was bacterial–virus coinfection. Conclusion mNGS has incremental application value in patients with CTD suspected of co-infection. It has a high sensitivity, and a wide detection range for microorganisms in CTD patients. Furthermore, the high incidence of opportunistic virus infections in CTD patients should be of sufficient concern.